Towards sustainable tourism through circular economy: The case of the Mekong Delta, Vietnam - Sen, Cao Thi; Hung, Tran Minh (Edelweiss Applied Science and Technology, 2025)
The research on the circular economy in tourism in the Mekong Delta focuses on developing a circular economy model within the tourism industry in this region. The goal of the study is to assess the potential, challenges, and propose solutions for developing the circular economy in Mekong Delta tourism. The research uses a qualitative approach, analyzing documents, legal frameworks, and relevant previous studies. The findings indicate that despite the Mekong Delta’s significant advantages in natural resources and cultural heritage, the development of circular tourism remains limited due to weak transportation infrastructure, inconsistent legal frameworks, and low awareness of the circular economy. The proposed solutions include complete the legal framework for the circular economy, develop infrastructure and apply green technology, raising awareness and educating communities on the circular economy, developing sustainable tourism linked to the circular economy, preserving and promoting ecological and cultural values, enhancing international cooperation and regional linkages in tourism development.